2019
DOI: 10.1126/scisignal.aav5918
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of ceramide 1-phosphate with group IVA cytosolic phospholipase A 2 coordinates acute wound healing and repair

Abstract: The sphingolipid ceramide 1-phosphate (C1P) directly binds to and activates group IVA cytosolic phospholipase A2 (cPLA2α) to stimulate the production of eicosanoids. Because eicosanoids are important in wound healing, we examined the repair of skin wounds in knockout (KO) mice lacking cPLA2α and in knock-in (KI) mice in which endogenous cPLA2α was replaced with a mutant form having an ablated C1P interaction site. Wound closure rate was not affected in the KO or KI mice, but wound maturation was enhanced in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 74 publications
(103 reference statements)
0
38
0
Order By: Relevance
“…The PLA2G2F, PLA2G4D, and PLA2G4E enzymes are part of the phospholipase A2 family, which has over 30 members, consisting of both cytosolic PLA2s (such as PLA2G4D and PLA2G4E), and secreted PLA2s (i.e., PLA2G2F), with variable expression of different members in a broad range of tissues (11,20). Studies have demonstrated that PLA2 enzymes regulate lipid pathways, and that many of these lipid species generated by these enzymes serve as bioactive mediators and essential components of the skin barrier (20,27). In addition, individual PLA2 enzymes exhibit unique tissue and cellular distribution, suggesting that they have distinct biological roles in production of pro-and anti-inflammatory lipid mediators (20,28).…”
Section: Discussionmentioning
confidence: 99%
“…The PLA2G2F, PLA2G4D, and PLA2G4E enzymes are part of the phospholipase A2 family, which has over 30 members, consisting of both cytosolic PLA2s (such as PLA2G4D and PLA2G4E), and secreted PLA2s (i.e., PLA2G2F), with variable expression of different members in a broad range of tissues (11,20). Studies have demonstrated that PLA2 enzymes regulate lipid pathways, and that many of these lipid species generated by these enzymes serve as bioactive mediators and essential components of the skin barrier (20,27). In addition, individual PLA2 enzymes exhibit unique tissue and cellular distribution, suggesting that they have distinct biological roles in production of pro-and anti-inflammatory lipid mediators (20,28).…”
Section: Discussionmentioning
confidence: 99%
“…Ceramide-1-phosphate (C1P), a sphingolipid-derived bioactive lipid, directly binds to and activates cPLA 2 α to stimulate the production of eicosanoids in vitro [ 86 ], but in vivo evidence for this event has been lacking. Recently, MacKnight et al [ 87 ] addressed this issue by generating knockin mice in which endogenous cPLA 2 α is replaced with a mutant form having an ablated C1P-interaction site. In a skin wound healing model, wound maturation, rather than wound closure, is enhanced in the mutant cPLA 2 α-knockin mice compared to control mice.…”
Section: The Spla 2 Familymentioning
confidence: 99%
“…Eicosanoid preparation and analysis. Eicosanoids were extracted using a modified extraction process and analyzed by UPLC ESI-MS/MS as previously described (14)(15)(16). Briefly, urine (4 mL) was combined with an IS mixture comprised of 10% methanol (400 ll) and glacial acetic acid (20 ll) before spiking with internal standard (20 ll) containing the following deuterated eicosanoids (2 pmol ll À1 , 40 pmol total) (all standards purchased from Cayman Chemicals): (d 4 ) Prostaglandin F 2 a, (d 4 ) Prostaglandin E 2 , (d 11 ) 5-iPF2a-VI, (d 4 ) 8-iso Prostaglandin F2a.…”
Section: Methodsmentioning
confidence: 99%
“…Eicosanoids were separated using a Shimadzu Nexara X2 LC-30AD coupled to a SIL-30AC auto-injector, coupled to a DGU-20A5R degassing unit in the following way as previously described by us (15,16). A 14-minute, reversed-phase LC method utilizing an Acentis Express C18 column (150 mm 9 2.1 mm, 2.7 lm) was used to separate the eicosanoids at a 0.5 ml min À1 flow rate at 40°C as previously described by our group (15,16). The column was equilibrated with 100% Solvent A [acetonitrile: water:formic acid (20:80:0.02, v/v/v)] for 5 min and then 10 ll of sample was injected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation